2010
DOI: 10.1158/1940-6207.capr-09-0059
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin and Celecoxib in Combination Inhibits the Progression of Androgen-Dependent LNCaP Xenograft Prostate Tumors to Androgen Independence

Abstract: Epidemiology studies suggest that statins and nonsteroidal anti-inflammatory drugs reduce the risk of prostate cancer. In the present study, LNCaP cells were cultured in regular medium containing fetal bovine serum or in medium supplemented with charcoal-stripped fetal bovine serum to mimic androgen deprivation treatment. We found that atorvastatin (Lipitor) or celecoxib (Celebrex) treatment of LNCaP cells cultured in regular or androgen-depleted medium inhibited growth and stimulated apoptosis. A combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 52 publications
(51 reference statements)
7
69
0
Order By: Relevance
“…Similar results were also obtained in xenograft models [47]. NSAIDs have also been shown to delay the progression of prostate tumors from androgen-dependent to androgen-independent growth [48]. NSAIDs delayed the regrowth of LNCaP xenografts in castrated SCID mice.…”
Section: Prostate Cancersupporting
confidence: 67%
“…Similar results were also obtained in xenograft models [47]. NSAIDs have also been shown to delay the progression of prostate tumors from androgen-dependent to androgen-independent growth [48]. NSAIDs delayed the regrowth of LNCaP xenografts in castrated SCID mice.…”
Section: Prostate Cancersupporting
confidence: 67%
“…18 This previous study concluded that decreased tumor growth in statin-treated animals was a result of increased apoptosis. Our study goes on to report that time to BCR following castration was significantly increased in the simvastatin-treated group, indicative of repressed AR reactivation and delayed castration-resistant progression of the xenografts.…”
Section: Discussionmentioning
confidence: 97%
“…17 In addition, atorvastatin treatment of castrated SCID mice harboring LNCaP xenografts resulted in decreased tumor growth that was correlated to an apoptotic response. 18 Finally, castration-resistant progression of LNCaP xenografts has been linked to intratumoural de novo steroidogenesis as well as to increased expression of cholesterol uptake and synthesis proteins. 6,19 We therefore hypothesized that simvastatin treatment may delay castration-resistant prostate cancer (CRPC) progression by blocking cellular cholesterol synthesis and therefore reducing de novo steroidogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This combination inhibited the progression of androgen-dependent LNCaP tumors to androgen independence and the growth of androgen-independent PC-3 prostate tumors in severe combined immunodeficient (SCID) mice more effectively than either agent alone. 22,23) Clinically, however, cardiac toxicity is a concern for celecoxib with long-term use increasing the risk of cardiovascular events limiting the development of the combination of atorvastatin and celecoxib in prostate cancer. …”
mentioning
confidence: 99%
“…This combination inhibited the progression of androgen-dependent LNCaP tumors to androgen independence and the growth of androgen-independent PC-3 prostate tumors in severe combined immunodeficient (SCID) mice more effectively than either agent alone. 22,23) Clinically, however, cardiac toxicity is a concern for celecoxib with long-term use increasing the risk of cardiovascular events limiting the development of the combination of atorvastatin and celecoxib in prostate cancer. 24) Based on epidemiologic evidence and the preclinical data for metformin and atorvastatin individually in prostate cancer, we assessed the effects of metformin and atorvastatin alone or in combination on cultured prostate cancer cells and in xenograft prostate tumors in SCID mice.…”
mentioning
confidence: 99%